Infant milk-feeding practices and diagnosed celiac disease and inflammatory bowel disease in offspring: a systematic review. (28th March 2019) - Güngör, Darcy; Nadaud, Perrine; Dreibelbis, Carol; LaPergola, Concetta C; Wong, Yat Ping; Terry, Nancy; Abrams, Steve A; Beker, Leila; Jacobovits, Tova; Järvinen, Kirsi M; Nommsen-Rivers, Laurie A; O'Brien, Kimberly O; et al.
ABSTRACT: Background: During the Pregnancy and Birth to 24 Months Project, the USDA and US Department of Health and Human Services initiated an evidence review on diet and health in these populations. Objective: The aim of these systematic reviews was to examine the relationships of never versus ever feeding human milk, shorter versus longer durations of any and exclusive human milk feeding, and feeding a lower versus a higher intensity of human milk to mixed-fed infants with diagnosed celiac disease and inflammatory bowel disease (IBD). Methods: The Nutrition Evidence Systematic Review team (formerly called the Nutrition Evidence Library) conducted systematic reviews with external experts. We searched CINAHL, Cochrane, Embase, and PubMed for articles published January, 1980 to March, 2016, dual-screened the results using predetermined criteria, extracted data from and assessed risk of bias for each included study, qualitatively synthesized the evidence, developed conclusion statements, and graded the strength of the evidence. Results: We included 9 celiac disease and 17 IBD articles. Limited case-control evidence suggests never versus ever being fed human milk is associated with higher risk of celiac disease, but concerns about reverse causality precluded a conclusion about the relationship of shorter versus longer durations of any human milk feeding with celiac disease. Evidence examining never versus ever feeding human milk and IBD was inconclusive, and limited, but consistent, case-control evidence suggests that, among infants fed human milk, shorter versus longer durations of any human milk feeding are associated with higher risk of IBD. For both outcomes, evidence examining the duration of exclusive human milk feeding was scant and no articles examined the intensity of human milk fed to mixed-fed infants. Conclusion: Limited case-control evidence suggests that feeding human milk for short durations or not at all associates with higher risk of diagnosed IBD and celiac disease, respectively. The small number of studies and concern about reverse causality and recall bias prevent stronger conclusions.